How much Priority Bonus Should be Given to Registered Donors? An Experimental Analysis - Annika Herr; Hans-Theo Normann (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2018)
Giving registered organ donors priority on organ waiting list can substantially increase the number of donors and save lifes. Evidence for these effects comes from recent experiments that implemented such priority rules in abstract laboratory environments. In these experiments, participants who registered as organ donors were fully prioritized over those who did not. In the field, however, registering as a donor is only one factor affecting the recipient's score. In this paper, we provide a comparative statics analysis of the priority treatment by varying the number of bonus periods that a registered person can skip on the waiting list. We find that behavior is monotonic: giving more priority to registered donors leads to higher registration rates. Our results also indicate that a medium sized bonus improves registration rates as much as absolute priority (used in the previous literature).
Keywords: C90; I10; I18; 330; organ donation; laboratory experiment; priority rule; waiting list